2020
DOI: 10.3390/s20195513
|View full text |Cite
|
Sign up to set email alerts
|

Sonomechanomyography (SMMG): Mapping of Skeletal Muscle Motion Onset during Contraction Using Ultrafast Ultrasound Imaging and Multiple Motion Sensors

Abstract: Background: Available methods for studying muscle dynamics, including electromyography (EMG), mechanomyography (MMG) and M-mode ultrasound, have limitations in terms of spatial resolution. Methods: This study developed a novel method/protocol of two-dimensional mapping of muscle motion onset using ultrafast ultrasound imaging, i.e., sono-mechano-myo-graphy (SMMG). The developed method was compared with the EMG, MMG and force outputs of tibialis anterior (TA) muscle during ankle dorsiflexion at different percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…This assessment, however, assumes that there is no lag between the generation of a contraction and the transmission of force to the tendon. More recent studies that have combined conventional bipolar EMG and ultrasound during voluntary contractions have found that fascicle shortening happen before force/torque is generated (Begovic et al , 2014; Ling et al , 2020), which agrees with our findings. Nevertheless, this assessment has several issues, first, the onset of muscle activation from bipolar EMG signals can be greatly influenced by the electrode’s location (Hug et al , 2011), second, fascicle shortening from deeper muscle regions could happen before EMG activity is detected on the surface (Dieterich et al , 2017) and third, the assessment can be confounded by the mechanical impedances of the measuring device (Corcos et al , 1992).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This assessment, however, assumes that there is no lag between the generation of a contraction and the transmission of force to the tendon. More recent studies that have combined conventional bipolar EMG and ultrasound during voluntary contractions have found that fascicle shortening happen before force/torque is generated (Begovic et al , 2014; Ling et al , 2020), which agrees with our findings. Nevertheless, this assessment has several issues, first, the onset of muscle activation from bipolar EMG signals can be greatly influenced by the electrode’s location (Hug et al , 2011), second, fascicle shortening from deeper muscle regions could happen before EMG activity is detected on the surface (Dieterich et al , 2017) and third, the assessment can be confounded by the mechanical impedances of the measuring device (Corcos et al , 1992).…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the current study, this previous research also revealed that fascicle shortening happens before force/torque is measured (3,34,58). However, the magnitude of these delays is considerably smaller than the ones presented herein, with ~6ms (EMG-FL) and ~12ms (EMGforce) of delay for electrically-induced contractions (34,44) and ~29ms (EMG-FL) and ~50ms…”
Section: Cst Fascicle Length and Torque Delayssupporting
confidence: 85%
See 1 more Smart Citation
“…The onset and peak points of various signals were identified within 2 s after the start of balance perturbation. The onset time of body CoM, body CoP, joint angle, joint moment, joint power, muscle EMG, and muscle MMG data was defined as the first time point when the corresponding normalized signal/data value went beyond five times of the standard deviation (SD) from the baseline value (mean + 5SD) [ 40 ]. The baseline value was calculated as the mean over the 1000-ms interval before the start of balance perturbation.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the non-invasive and real-time ultrasound shear-wave elastography (SWE) has become a popular and useful tool for assessing muscle stiffness [ 23 , 24 ]. For this technology, the ultrasound probe can induce a focused acoustic force and create a shear wave within the target tissue [ 25 , 26 ]. By capturing the propagation of the shear wave, the speed of the shear wave propagation (c) can be calculated, which can then be squared and multiped by three and the muscle mass density (ρ = 1000 kg/m 3 ) to calculate the muscle elasticity (assumed as E = 3ρc 2 ) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%